Problematika Kebijakan Pembangunan dan Pemeliharaan Infrastruktur Jalan di Provinsi Banten - Dede Qodrat Alwajir (Public Service and Governance Journal, 2022)
Road infrastructure is a public good whose existence must be felt by all levels of society. Road infrastructure development is a policy that deserves attention from the government, including in the Banten Province region. This research aims to explain the problems in development and maintenance policies for road infrastructure in Banten Province. The research method uses a qualitative approach. Based on research, it is known that the implementation of road infrastructure development and maintenance policies in Banten Province has not been carried out optimally because it has not yet provided significant changes and minimized existing problems. Some of the problems include the government's responsiveness in dealing with road problems which is still lacking, resulting in victims due to reports not being resolved immediately. The inhibiting factors in implementing the development and maintenance of road infrastructure in Banten Province include a lack of skilled human resources, erratic activities due to policy changes in different central and regional government periods, and natural factors.